Regulation of Macrophage and Dendritic Cell Function by Chondroitin Sulfate in Innate to Antigen-Specific Adaptive Immunity - Hatano, Sonoko; Watanabe, Hideto (Frontiers in Immunology, 2020)
Chondroitin sulfate (CS), a type of glycosaminoglycan (GAG), is a linear acidic polysaccharide comprised of repeating disaccharides, modified with sulfate groups at various positions. Except for hyaluronan (HA), GAGs are covalently bound to core proteins, forming proteoglycans (PGs). With highly negative charges, GAGs interact with a variety of physiologically active molecules including cytokines, chemokines and growth factors, and control cell behavior during development and in the progression of diseases including cancer, infections, and inflammation. Heparan sulfate (HS), another type of GAG, and HA are well reported as regulators for leucocyte migration at sites of inflammation. There have been many reports on the regulation of immune cell function by HS and HA, however, regulation of immune cells by CS has not yet been fully understood. This article focuses on the regulatory function of CS on antigen-presenting cells, including macrophages and dendritic cells, and refers to CSPGs, such as versican and biglycan, and cell surface proteoglycan, syndecan.